Population Parameters and Feeding Preference of Spodoptera litura (Lepidoptera: Noctuidae) on Different Asparagus officinalis Tissues - Li-Min Ye; Xue-Yuan Di; Bin Yan; Jian-Feng Liu; Xiu-Qin Wang; Mao-Fa Yang (Insects, 2022)
Spodoptera litura is an important pest that seriously affects Asparagus officinalis production. To clarify the population characteristics and feeding preference of S. litura on different asparagus tissues, asparagus stems and leaves were selected as the research objects, related studies were conducted by constructing the life table and the feeding preference experiment. The results showed that S. litura could complete its development and reproduction normally on asparagus stems or leaves. Although the adult longevity and fecundity of S. litura on the two types of tissues were not significantly different, the development duration of larvae and pupae, and total preoviposition period on leaves were significantly longer than those raised on stems. The intrinsic rate of increase and finite rate of increase were 0.186 d−1 and 1.204 d−1 on stems, which were significantly higher than those fed on leaves (0.161 d−1 and 1.175 d−1). The mean generation time on stems (32.88 d) was significantly lower than on leaves (36.88 d). It indicated that stems were more suitable for its population growth. In the feeding preference, the third and fifth instar larvae preferred to feed on leaves, and other instar larvae (except for the sixth instar of 2.5 h) had no significant difference. These results will provide a theoretical reference for further research and forecasting and integrated control.